Bernard A. Schriever papers - Schriever, Bernard A.; Ford, Vincent, 1907-2001.
Correspondence, memoranda, speeches, writings, reports, subject files, and other papers relating to Schriever's career as a U.S. Air Force officer responsible for the research and development of the intercontinental ballistic missile (ICBM) and early military space programs and to his post-military career as a corporate and government consultant. Documents his work as head of the U.S. Air Force Western Development Division and the U.S. Air Force Air Research and Development Division, later the Air Force Systems Command. Also documents Schriever's post-military activities relating primarily to his service as an advisor to the U.S. Air Force and U.S. Dept. of Defense; his work on groups such as the U.S. National Commission on Space, U.S. President's Advisory Council on Management Improvement, President's Foreign Intelligence Advisory Board, and the President-elect's Advisory Task Force on Science and Technology for Ronald Reagan; his record production company, Virgo Company, promoting the career of his wife and singer, Joni James; and reunions of the U.S. Army Air Corps Advanced Flying School (Kelly Field, Tex.). Includes the draft of a book concerning the ICBM program by Schriever and S.T. Cohen and papers (1939-1976) of Vincent Ford relating primarily to his service as an associate of Schriever in the air force and to his history of the ballistic missiles program.
Subjects include air force planning, management, and organization; air force research, development, and acquisition issues; arms and armaments; ballistic missiles and missile defense; military strategy; national security; Project Forecast; Ramo-Wooldridge Corporation and Space Technology Laboratories; satellites including reconnaissance satellites; space issues and policy; technology; use of systems management approach in solving urban problems; the Cold War; and following the collapse of the Soviet Union, Russian-American initiatives including the Russian-American Observational Satellites (RAMOS) project.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
U.S. Air Force officer, aviator, and aerospace consultant. Born 1910; died 2005.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: James, Joni; Cohen, S. T; Reagan, Ronald; United States; United States. -- Air Force -- Management; United States. -- Air Force -- Operations other than war; United States. -- Air Force -- Planning; United States. -- Air Force -- Procurement; United States. -- Air Force -- Research; United States. -- Air Force. -- Air Research and Development Command; United States. -- Air Force. -- Systems Command; United States. -- Air Force. -- Western Development Division; United States. -- Army. -- Air Corps. -- Advanced Flying School (Kelly Field, Tex.); United States. -- Department of Defense; United States. -- National Commission on Space; United States. -- President's Advisory Council on Management Improvement; United States. -- President's Foreign Intelligence Advisory Board; President-elect's Advisory Task Force on Science and Technology; Project Forecast; Ramo-Wooldridge Corporation; Russian-American Observational Satellites; Space Technology Laboratories, inc; Virgo Company; Astronautics, Military -- United States; Ballistic missiles; Cold War; Intercontinental ballistic missiles; Military intelligence -- United States; Military weapons; National security -- United States; Satellites; Space surveillance; Strategy; Technology; Urban policy; World politics -- 1945-1989.; Russia -- Foreign relations -- United States; Soviet Union -- Foreign relations -- United States; United States -- Foreign relations -- Russia; United States -- Foreign relations -- Soviet Union; United States -- Military policy; Air Force officers; Aviators; Consultants